PROTOTIPE SMART HOME DENGAN IoT (INTERNET of THINGS) BERBASIS WEMOS D1 MINI - Rendy Fadli Iswara; Mulkan Iskandar Nasution; Nazaruddin Nasution (JISTech (Journal of Islamic Science and Technology), 2022)
Research has been carried out prototype Smart home with IoT (Internet of Things) based on Wemos D1 Mini which can simulate the application of Smart home that can be accessed via the internet by connecting electronic devices to the internet with a Wemos D1 mini microcontroller, while processing all data in the form of input and output. , with control system via wemos and supported by MQ-2 sensor, flame sensor, PIR sensor, relay, buzzer, water pump and fan. The method applied in this research is the monitoring and control system development carried out in this study, namely: the design is equipped with several features, namely sending notifications to the SmartPhone in the form of reports and settings through the application so that it can help users to find out and get information about the conditions that occur at home. , this design is also equipped with an MQ-2 sensor when the sensor detects the 5V fan will turn on to suck gas / smoke out of the room, as a continuation if a gas leak occurs, this prototype is also equipped with a Flame sensor which can turn on the water pump as a fire suppression by The concentration of the sensor works at a wavelength of less than 450 nm, it is also equipped with a PIR Sensor that will turn on an alarm if an intruder is detected in the house and on the tile.